Manajemen Sarana Dan Prasana Dalam Peningkatan Mutu Pendidikan Di MTsN 1 Jombang - Muhammad Rizqi Ismail; Nur ‘Azah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2023)
This research aims to describe the management and maintenance of assets and facilities, as well as the supporting and inhibiting factors in the management of advice and facilities in MTsN 1 Jombang. This research includes qualitative case studies. Data is collected through observation methods, question answers, and documentation. The results of this research show that: 1) The management of assets and stocks in MTsN 1 Jombang covers the stages of planning, procurement, inventory, use, disposal, and storage. 2) In terms of its maintenance, it involves the resources that exist in the school, not only the wakamad, but all of them play a role in safeguarding the means and facilities that it owns. 3) As to the inhibitory factor of its own resources, such as no care for the facilities and facilities of the madrasah, the supporting factor of the SDM is the main factor in supporting the success of the programmes that have been held by the madrasah.